High incidence of human papillomavirus infection in cervical carcinoma patients in South Hungary - Kalmár, László (Acta Biologica Szegediensis, 2005)
The aim of this study was to determine the incidence of human papillomavirus (HPV) in cervical carcinoma patients. A nested case-control study was performed to investigate the relationship between HPV infection and cervical carcinoma. A total of 347 women 169 of whom gave abnormal Pap smear tests; were recruited to participate in the study; 39 of them suffered from invasive carcinoma. The overall incidence of HPV infection in the cancer, positive cytology and normal cytology groups was 74% (29/39), 55% (72/130) and 4% (7/178), respectively (p<0.001). The risk for progression to cervical carcinoma when the HPV infection was associated with abnormal cytology was 2.16 (95%, CI: [1.01-4.69]). The incidence of HPV infection associated with abnormal cytology correlated significantly with the presence of cervical carcinoma.